Peran Ulumul Qur’an dalam Meningkatkan Literasi Keagamaan Peserta Didik: The Role of the Ulumul Qur'an in Increasing Students' Religious Literacy - Hukaimah; Istiana; Afina Mahbubah (Litera Academica Publishing, 2025)
Ulumul Qur’an is a branch of Islamic knowledge that explores essential aspects of understanding the Qur’an in depth. The integration of Ulumul Qur’an into Islamic education is believed to enhance students' religious literacy, encompassing their ability to read, comprehend, and apply the teachings of the Qur’an in daily life. This article aims to analyze the role of Ulumul Qur’an in improving students' religious literacy through a literature review of various scholarly journals. The findings indicate that a strong understanding of Ulumul Qur’an can reinforce religious character, deepen comprehension of Islamic teachings, and shape attitudes and behaviors aligned with Qur’anic values.